MONETARY POLICY AND THE PERFORMANCE OF STOCK MARKET IN NIGERIA - Tubotamuno, Boma; Oladosu, Isaac Olubiyi (African Journal of Social and Behavioural Sciences, 2024)
This study empirically determined the effect of monetary policy on the performance of the stock market in Nigeria from 1985 to 2022. The monetary policy rate, money supply, lending rate and treasury bill rate were used as proxies for monetary policy while stock market performance was measured by stock market capitalisation. The time series data used for the study were sourced/extracted from the Central Bank of Nigeria (CBN) statistical bulletin. The techniques of data analysis adopted include descriptive statistical techniques, the ADF unit root test, and the ARDL approach. The results of the study showed that the monetary policy rate has a negative and nonsignificant effect on stock market capitalisation in Nigeria, the money supply and the treasury bill rate have a positive and significant effect on stock market capitalisation in Nigeria while the lending rate has a negative but significant effect on stock market capitalisation in Nigeria. Based on the findings, the study concluded that monetary policy variables are vital determinants of the performance of the stock market in Nigeria. The Central Bank of Nigeria should be cautious and properly consider the prevailing macroeconomic conditions in monetary policy decisions, especially with regard to the lending rate because of its potential to fuel inflation, which negatively affects the performance of the stock market.